Correlation between the physical activity volume and cognitive and mental capacity among older adult people in China: a cross-sectional study based on the 2020 CHARLS database - Shixin Li; Jiayi Zhang; Yonghong Yang; Yonghong Yang (Frontiers Media S.A., 2024)
BackgroundCurrently, due to the progress of the aging population in China and the government's attention to healthy aging, there is an increasing emphasis on the cognitive function and psychological function of older adult people. Therefore, the aim of our study was to investigate the relationships between physical activity and cognitive and psychological function in order to provide recommendations for exercise guidance.MethodsThe Center for Epidemiologic Studies Depression Scale (CESD-10) was used to assess mental capacity, and cognitive function was evaluated across three domains: orientation, memory and calculation. Total physical activity data were obtained via interviews. Ability of Daily Living (ADL) and Instrumental Ability of Daily Living (IADL) scores were used to determine the presence or absence of daily physical function impairment. Finally, we conducted correlation analysis and logistic regression on participants' physical activity volume (PAV) and their cognitive and psychological functions, respectively.ResultsA total of 5,871 participants who met the inclusion criteria were selected from the China Health and Retirement Longitudinal Study (CHARLS). The prevalence of depression was 8.1, and 31.6% of the older adult participants reported experienced depressive symptoms. Additionally, 15.6% of the older adult individuals had insufficient weekly physical activity, while 3.9% had daily physical function (DPF) impairment. Physical activity volume (PAV) was negatively correlated with the CESD-10 score, as well as with orientation, calculation, and memory.ConclusionOur study confirmed that inactive weekly physical activity was associated with an increased risk of depression, cognitive impairment, and DPF impairment among older adult individuals in China.